A New Management da intervenção social: perceção dos riscos psicosso-ciais e ambientais no acolhimento social e os fatores de bem-estar para os interventores sociais: https://doi.org/10.53809/TS_ISS_2023_n.4_141-157 ("Temas Sociais" Journal, 2023)
This article presents an analysis of the relationship between psychosocial risks, highlighting the management of the intervention, a theoretical framework that underpins some of the factors analysed in the doctoral research, which aims to assess the working conditions in the context of the action of first-line interveners in social reception. To obtain these data, a questionnaire was applied to obtain information on the perception of social workers in the various aspects of their professional daily lives that influence their health and well-being. It is concluded that it is necessary to enable professionals with stress-coping strategies, such as engagement - by analysing positive experiences and conditions favourable to well-being in the workplace (Extremera et.al., 2005; Gonçalves, 2020); coping (adaptation to circumstances and situations); supervision; triggering (good) social support; as well as working and applying in practice individual characteristics and physiological release mechanisms, complemented by a resilient posture and locus of control, adaptation to change, overcoming obstacles and resistance to pressure (Gonçalves, 2020, p.28; Fernandez-Barrocal, 2021).
Keywords: Social work; Social care; Psychosocial risks; Stress management; Coping.